2021
DOI: 10.1021/acsmaterialslett.1c00724
|View full text |Cite
|
Sign up to set email alerts
|

Using Molecules with Superior Water-Plasticity to Build Solid-Phase Molecular Self-Assembly: Room-Temperature Engineering Mendable and Recyclable Functional Supramolecular Plastics

Abstract: The brittleness of many supramolecular films in a dry environment has prevented their further application as supramolecular plastics. We report here the fabrication of supramolecular plastics displaying excellent dry-flexibility and mechanical strength through room-temperature solid-phase molecular self-assembly using water-locking polyelectrolyte and surfactant. Aided by mild mechanical pressure of about 0.5 MPa, the locked water enables the polyelectrolyte-bridged surfactant microdomains to merge into large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Recently, Yan et al found that molecules in the precipitates formed with the aqueous mixture of ionic surfactant and oppositely charged polyelectrolyte may undergo self-assembly to form large-area self-supporting films under pressure in the presence of a tiny amount of water. The driving forces for the multiscale self-assembly process are mainly the hydrophobic interaction between surfactant molecules. The electrostatic interaction between the polyelectrolyte chain and surfactant molecules is to endow the film with the self-supporting ability through the cross-linking of nanodomains formed by surfactants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Yan et al found that molecules in the precipitates formed with the aqueous mixture of ionic surfactant and oppositely charged polyelectrolyte may undergo self-assembly to form large-area self-supporting films under pressure in the presence of a tiny amount of water. The driving forces for the multiscale self-assembly process are mainly the hydrophobic interaction between surfactant molecules. The electrostatic interaction between the polyelectrolyte chain and surfactant molecules is to endow the film with the self-supporting ability through the cross-linking of nanodomains formed by surfactants.…”
Section: Resultsmentioning
confidence: 99%
“…However, so far most molecular self-assemblies are obtained in the form of solution-based colloidal dispersions. This solution-based molecular self-assembly is hard to work with when bulk macroscopic materials are required . To tackle this problem, we recently developed a strategy of solid-phase molecular self-assembly (SPMSA), with which supramolecular films can be obtained at large scales . This not only allows the preparation of noncolloidal form self-supporting macroscopic molecular self-assembled materials but also makes it possible to achieve diversified functions. ,, …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations